Thai University Students’ Attitudes Toward Online Language Learning in a Time of Crisis - Kerry Pusey (2022)
In the wake of the COVID-19 pandemic, transitions to online L2 learning have rapidly emerged. However, the impacts of these transitions on students’ attitudes toward online language learning are largely unknown. This study investigated how participation in remote EAP instruction impacted the attitudes of Thai university students (n = 263) toward online language learning. The study employed a longitudinal survey design and utilized a questionnaire instrument designed for the study containing 33 Likert scale items. The questionnaire was administered at the beginning and end of students’ first fully remote semester. Within- and between-groups comparisons were made of participants’ mean attitudinal ratings on eight multi-item subscales to measure the extent to which, and in what ways, students’ attitudes changed over time. Statistically significant differences were evident in the subscales of open-mindedness, autonomy, effectiveness of instruction, interactivity, and engagement over time; the general trend was toward a more positive perspective on online learning. Results indicated no statistically significant differences on three of the multi-item subscales (motivation, anxiety, and convenience) over time. The analysis showed a significant interaction between proficiency level and time in ratings for the effectiveness of instruction subscale only. Most subscales were weakly correlated with motivation at the beginning of the term; however, all subscales except interactivity showed a higher correlation at the end of the term. The results of this study will be of interest to educators who are seeking to understand learners’ attitudes toward online language instruction during times of crisis and emergency remote teaching (ERT).